Aktivitas Insektisida Campuran Ekstrak Air Buah Piper aduncum L. (Piperaceae) dan Batang Cymbopogon ciratrus (Dc.) Stapf (Poaceae) Terhadap Larva Crocidolomia pavonana F. (Lepidoptera: Crambidae) - Lina, Eka Candra; Supriadi, Adventus; Yunisman, Yunisman; Martinius, Martinius (Plant Protection Department, Faculty of Agriculture, Universitas Andalas, 2017)
Crocidolomia pavonana is an important pest in Brassicaceae. Botanical insecticides is pest control alternative which meet to eco-friendly manajement. This study aims to determine lethal concentration of single and mixture of water extract of Piper aduncum (Piperaceae) fruit and Cymbopogon cirtatus (Poaceae) stem against Crocidolomia pavonana larvae. The study was conducted in laboratory experiment through preliminary test and advance test using a completely randomized design (CRD). Observations were included to larval mortality, antifeedant effect, and duration of larval development. Bioassay was done against second instar larvae of C. pavonana using leaves immersion method during 48 hours. The results show that LC50 and LC95 value of mixture extract are 2.83% and 5.79% respectively. Based on index combination analysis, P. aduncum and C. citratus mixture extract were antagonistic at LC50 and additive at LC95 . Water extract of P. aduncum and C. citratus were relatively weak to influence feeding activity of C. pavonana larvae (41%). Mixture extract also extend larval development from second instar to third instar around 0.24 days and third instar to fourth instar around 0.97 days.